1997
DOI: 10.1016/s0009-2509(97)00268-6
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics applied to gas-liquid contactors

Abstract: Abstract-In this paper a "hierarchy of models' is discussed to study the fluid dynamic behaviour of gas-liquid bubble columns. This 'hierarchy of models' consists of a Eulerian Eulerian two fluid model, a Eulerian-Lagrangian discrete bubble model and a Volume Tracking or Marker Particle model. These models will be briefly reviewed and their advantages and disadvantages will be highlighted. In addition, a mixed Eulerian Lagrangian model and a volume tracking model, both developed at Twente University, will be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(82 citation statements)
references
References 30 publications
1
81
0
Order By: Relevance
“…The results compare favorably with the numerical predictions of Delnoij et al (1998) who found a qualitative agreement with available experimental data.…”
Section: Merger Of Two Bubblessupporting
confidence: 81%
“…The results compare favorably with the numerical predictions of Delnoij et al (1998) who found a qualitative agreement with available experimental data.…”
Section: Merger Of Two Bubblessupporting
confidence: 81%
“…The former treats the droplets as an effective continuum and is in essence a generalized two-fluid model (Ishii 1975;Bennon & Incropera 1987). The latter recognizes the necessity of tracking discrete droplets, and achieves this by using correlations, say, for the drag and lift coefficients (Delnoij, Kuipers & van Swaaij 1997). In both models, the mass, momentum and heat transfer between the gas and the droplets must be provided as inputs; these may come from experimental data, phenomenological calculations using, say, the cell model (Bellan 1991), or accurate calculations for a single droplet (Sirignano 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In the volume of fluid (VOF) formulation, [16], for multiphase fluid dynamics the fluids are not interpenetrating. For each phase, a variable is introduced: the volume fraction of the phase in the computational cell.…”
Section: Mathematical Model and Geometrymentioning
confidence: 99%
“…The pressure velocity coupling is obtained using the SIMPLEC algorithm. We use the geometrical reconstruction scheme to obtain the faces fluxes, when the cell is near the interface between two phases; this scheme represents the interface between fluids using a piecewise-linear approach [16]. For the time-dependent VOF calculations, we use a second order implicit time-marching scheme with a convergence criteria of 0.001 and with a time step Δ = 1 × 10 −4 s. The algorithm used for pressure discretization was PRESTO, and for the momentum, turbulent kinetic energy and its dissipation rate equations second order upwind scheme were used [17].…”
Section: Numerical Setupmentioning
confidence: 99%